Pengaruh Pendidikan Agama Islam di Lingkungan Sekolah dan Lingkungan Keluarga terhadap Sikap Toleransi Beragama Siswa SMAN 1 Bengkulu Utara - Apdila Nursanti; Qolbi Khoiri; Dayun Riadi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to: (1) determine whether there is an influence of Islamic religious education in the school environment on the religious tolerance attitude of students at SMA Negeri 1 Bengkulu Utara, (2) determine whether there is an influence of Islamic religious education in the family environment on the religious tolerance attitude of students at SMA Negeri 1 Bengkulu Utara, and (3) determine whether there is an influence of Islamic religious education in both the school and family environments on the religious tolerance attitude of students at SMA Negeri 1 Bengkulu Utara. This research uses a quantitative approach. Data collection was conducted using a questionnaire, with a total of 91 respondents. The results of the data analysis indicate that: (1) there is an influence of Islamic religious education in the school environment on students' religious tolerance attitude at SMA Negeri 1 Bengkulu Utara, with a coefficient of 0.148 and a t-value of 4.443, which is greater than the t-table value of 1.66235 (t_calculated > t_table); (2) the influence of Islamic religious education in the family environment on students' religious tolerance attitude at SMA Negeri 1 Bengkulu Utara is 0.462, with a t-value of 4.173, which is greater than the t-table value of 1.66235 (t_calculated > t_table); and (3) the simultaneous (combined) influence of Islamic religious education in both the school and family environments on students' religious tolerance attitude at SMA Negeri 1 Bengkulu Utara is 0.584, with an F-value of 9.889, which is greater than the F-table value of 3.097 (F_calculated > F_table), and a significance level of 0.000 < 0.05.